Case report of proton pump inhibitor responsive esophageal eosinophilia: why 2 months of proton pump inhibitors is required. Issue 6 (1st September 2016) - Lipka, S.; Muhammad, A.; Champeaux, A.; Richter, J. E.
Summary: Eosinophilic esophagitis (EoE) is a chronic inflammatory disease defined by the 2nd EoE consensus panel as: 'symptoms related to esophageal dysfunction, ≥15 eosinophils per high-power field, eosinophilia that persists after a trial of proton pump inhibitor (PPI) therapy, and exclusion of other secondary causes of esophageal eosinophilia'. After Ngo et al . first reported a case series of 3 patients initially diagnosed with eosinophilic esophagitis responding endoscopically and histologically to PPI therapy, the term PPI-responsive esophageal eosinophilia has evolved. Several studies have since confirmed the existence of this entity. Although recent ACG guidelines call for a 2-month course of PPI followed by endoscopy biopsies this recommendation is classified as a strong recommendation with 'low evidence', and has not been proven in the literature. We present a case of PPI-REE treated with rabeprazole 20 mg BID for 2 months, and describe simultaneous symptom resolution with histological and endoscopic remission of disease. This unique case with serial endoscopy and histology at baseline and monthly suggests the current recommendation of at least two months therapy with PPIs dosed twice daily is appropriate. Future studies will need to address duration of high dose therapy, whether patients can be stepped down to once a day PPI, and therapeutic strategy for transient responders.